Pengaruh Model Pembelajaran Learning Cycle 7E dengan Menggunakan Media Wordwall terhadap Kemampuan Berpikir Kritis Peserta Didik pada Mata Pelajaran Geografi - Widya Maritza; Syairul Bahar; Andri Noor Ardiansyah (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
This study aims to determine the effect of the Learning Cycle 7E model assisted by Wordwall media on students’ critical thinking skills. This study employed a quantitative approach with a quasi-experimental design. The sample consisted of grade XI students of SMA Negeri 5 Depok, with class XI.5 as the experimental group and class XI.8 as the control group. The research instruments were a critical thinking skills test consisting of 10 essay questions and a student response questionnaire. Data analysis was conducted through the Shapiro-Wilk normality test, the Levene homogeneity test, and hypothesis testing using the Independent Sample T-Test with a significance level of 0.05. The results indicated a significant difference in critical thinking skills between the experimental and control groups. This finding was supported by the significance value (Sig. 2-tailed) of 0.021 < 0.05, which means H₀ was rejected and H₁ was accepted. Furthermore, the average post-test score of the experimental class was 83.29, higher than that of the control class, which was 79.11. Thus, the implementation of the Learning Cycle 7E model assisted by Wordwall media has a positive and significant effect on students’ critical thinking skills in Geography subjects.